The outcomes in children with Hirschsprung’s disease treated with transanal endorectal pull-through method - Szymczak, Artur; Ogorzałek, Anna; Leksa, Natalia; Sęk-Mastej, Anna; Orkisz, Stanisław (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The evaluation of functional results, complications and problems of children with Hirschsprung’s disease treated with one-stage surgery (TEPT) or two-stage surgery (colostomy, TEPT) in Paediatric Surgery Clinic in Rzeszów. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Medical documentation of 41 children treated due to Hirschsprung’s disease in years 2006-2018 in Rzeszów were retrospectively analysed. The results of the questionnaires conducted among the parents of operated children were surveyed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The average time of the radical surgery was 189 minutes. The mean length of the resected intestine in the classic form was 19 centimeters, in long-segment 35 centimeters. In the post-operative period, 15 patients had a blood transfusion. The mean time of the children’s stay calculated from the date of surgery until the discharge equaled 13.4 days. Early post-operative complications: enterocolitis occurred in 6 patients (1 death in a septic shock mechanism), total dehiscence of anastomosis in 1 patient, abscess of perirectal space in 1 patient, anastomotic retraction in 1 patient and in 3 patients inaccurate intra-operative evaluation of the section (intra), buttock dermatitis appeared in all patients. Late post-operative complications (a control trial of 38 patients): Soiling was confirmed in 9 patients, periodic constipation in one. The abnormal consistency of stool was signaled in 3 children. Two children were repetitively hospitalized due to enterocolitis. The frequency of defecation almost in all patients was reduced after a three, four-month period since the operation from 10-15 per day to the age norm. In one child, where the retraction of the anastomosis was diagnosed, the soiling and heightened frequency of defecation throughout the day persists. All of the parents of the older children view the outcome of the surgery as positive and the life quality of their children does not differ from their peers. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. TEPT is a method which can be performed in newborns, infants, babies as well as in case of a long-segment aganglionosis. Barium enema is not reliable in evaluation of the length of the aganglionic section in the long-segment type of Hirschsprung’s disease. The treatment of choice in the early post-operative enterocolitis should be colostomy. Worse functional results were observed in children after two-stage treatment – especially, in cases where the colostomy was created due to the intestinal re-distention.